RBFNN versus GRNN modeling approach for sub-surface evaporation rate prediction in arid region - Kamel A.H.; Afan H.A.; Sherif M.; Ahmed A.N.; El-Shafie A. (Elsevier Inc., 2023)
Arid regions; Forecasting; Gravel; Radial basis function networks; Reservoirs (water); Soils; Stochastic systems; Wind; Accurate prediction; Correlation coefficient; Generalized Regression Neural Network(GRNN); Nonlinear process; Prediction accuracy; Radial basis function neural networks; Statistical indicators; Subsurface reservoir; Evaporation